Genetic and ecological research on anisakid endoparasites of fish and marine mammals in the Antartic and Artic-Boreal regions. - BULLINI, Luciano; CIANCHI, Maria Rossella; D'AMELIO, Stefano; MATTIUCCI, Simonetta; PAGGI, Lia; P. Arduino; G. Nascetti; P. Orecchia; J. Plotz; B. Berland; J. w. Smith; J. Brattey (Cambridge University Press, 1997)
Data are presented on the genetics and ecology of fish and marine mammal anisakid parasites of the genera Contracaecum, Pseudoterranova and Anisakis from the Antarctic and Arctic-Boreal regions. The three morphospecies C.osculatum, P.decipiens and A.simplex, considered cosmopolitan and euriecious, were each shown by isozyme analysis to include a number of sibling species, differentiated genetically and ecologically. The reproductive isolation of C.raadiatum, an Antarctic species often confused with C.osculatum s.l. was also shown. The C.osculatum-radiatum, P.decipiens and A.simplex complexes achieved a bipolar distribution at different times, from 5-6 to about 1 million years ago, through distinct colonizations of the Antarctic region. The more ancient bipolar distribution (C.radiatum, P.decipiens E) coincides with that of the first colonization of the Antarctic by seals; the more recent one (C.osculatum E) occurred in the Pleistocene. In the three anisakid complexes, Antarctic species show a higher genetic variability than the Boreal ones (average He = 0.21 and 0.14, respectively). This is apparently related to a lower habitat disturbance of the Antarctic region, allowing species to reach higher population sizes, with a lower probability of genetic drift phenomena. In both the Arctic-Boreal and Antarctic regions, differences in host preferences were seen which could be related both to differential host-parasite coadaptation and coevolution and to interspecific competition.